PENGARUH KEPEMIMPINAN DAN LOCUS OF CONTROLTERHADAP KINERJA PEGAWAI DENGAN MODERASI BUDAYA ORGANISASI ( Studi Pada Sekretariat DaerahKabupaten Rembang ) - Aris Gunawan Wijanarko, 11.42, 02. 0029 (Students Journal of Economic and Management, 2013)
The purpose of this study is to analyze the effects of leadership and Locus of Control on the employeeâs job performance with organizational culture as moderator in Rembang Regional Administration Secretariat.The independent variablesÂ thatÂ are presumed to affect the job performance in this study is restricted to leadership and locus of controlÂ with organizational culture as the moderating variable. The data collection in this study was held in February 25th to March 5th 2013, with the civil servantÂ of Rembang Regional Administration Secretariat as the population that amounts to 234 people.Â This studyÂ use proportional sampling, where the random samples are taken of each stratum proportionally.Â Samples are taken using proportional methode by distributing questionnaires : 113 questionnaires were returned andÂ filled correctly by respondents according to filling instruction and 7 questionnaires were not returned. This study using statistical tests including validity test with factor analysis, reliability test using Cronbachs alpha, double regression analysis, and significance test using the coefficient of determinationto prove the validity of hypothesis andÂ moderation tests. The results of this study proved that modelâs ability in explain correctly , the effectÂ of leadership and organizational culture variable to job performance and moderation interaction of leadership and organizational culture variable ( equation II) is amount 42,7% to job performance . Whereas the modelâs ability in explain correctly the effect of locus of control and organizational culture variable (equation III) is amount 31,6% to job performance. Moderating effect test proved that organizational culture has significant moderating effects on leadership to job performance, but not locus of control. Keywords : Leadership, Locus of Control, Organizational Culture and Job Performance.